Effect of Trans-Anethole on Gene Expression of Steroidogenic Enzymes in the Ovary of Polycystic Ovary Syndrome Model Rate: - Asadian, Maryam; Yaghoubi, Hashem; Mahmoudi, Fariba; Haghighat Gollo, Khadijeh (Galen Medical Journal, 2022)
Background: The process of steroidogenesis is crucial to the normal function of the ovaries. In individuals with polycystic ovary syndrome (PCOS), the activity of related enzymes in this process is disrupted. In the present study, the effect of trans-anethole was investigated on gene expression of steroidogenesis enzymes in PCOS model rats. Materials and Methods: In this experimental study, thirty female rats were divided into six groups (n=5 per group). Fifteen PCOS rats in three groups received intraperitoneal injections of distilled water, 50, and 80 mg/kg of trans-anethole, respectively. Also, 15 intact rats in three groups received intraperitoneal injections of distilled water, 50, and 80 mg/kg trans-anethole. The expression of steroidogenesis genes was determined using real-time reverse transcription polymerase chain reaction. Results: The mRNA level of Cyp19 significantly increased in intact rats receiving 80 mg/kg trans-anethole compared to the control group. The Cyp19 level in PCOS groups was significantly reduced compared to the control group. The mRNA level of Cyp19 in PCOS groups that resived 50 or 80 mg/kg trans-anethole increased compared to PCOS rats, but this increase was not statistically significant. The mRNA level of Cyp17 did not significantly change in intact and PCOS rats that received trans-anethole compared to the control group. Conclusion: Trans-anethole may improve PCOS complications due to its involvement in regulating steroidogenesis.